Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài giải:
a) x3 + 2x2y + xy2– 9x = x(x2 +2xy + y2 – 9)
= x[(x2 + 2xy + y2) – 9]
= x[(x + y)2 – 32]
= x(x + y – 3)(x + y + 3)
b) 2x – 2y – x2 + 2xy – y2 = (2x – 2y) – (x2 – 2xy + y2)
= 2(x – y) – (x – y)2
= (x – y)[2 – (x – y)]
= (x – y)(2 – x + y)
c) x4 – 2x2 = x2(x2 – (√2)2) = x2(x - √2)(x + √2).
a) x3 + 2x2y + xy2– 9x = x(x2 +2xy + y2 – 9)
= x[(x2 + 2xy + y2) – 9]
= x[(x + y)2 – 32]
= x(x + y – 3)(x + y + 3)
b) 2x – 2y – x2 + 2xy – y2 = (2x – 2y) – (x2 – 2xy + y2)
= 2(x – y) – (x – y)2
= (x – y)[2 – (x – y)]
= (x – y)(2 – x + y)
c) x4 – 2x2 = x2(x2 – (√2)2) = x2(x - √2)(x + √2).
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 3( x - y ) - 5x( y - x )
= 3( x - y ) - 5x[ -( x - y ) ]
= 3( x - y ) + 5x( x - y )
= ( 3 + 5x )( x - y )
b) x3 + 2x2y + xy2 - 9x
= x( x2 + 2xy + y2 - 9 )
= x[ ( x + y )2 - 32 ]
= x( x + y - 3 )( x + y + 3 )
c) 14x2y - 21xy2 + 28x2y2
= 7xy( 2x - 3y + 4xy )
Bài giải
\(a,\text{ }3\left(x-y\right)-5x\left(y-x\right)\)
\(=3\left(x-y\right)+5x\left(x-y\right)\)
\(=\left(x-y\right)\left(3+5x\right)\)
\(b,\text{ }x^3+2x^2y+xy^2-9x\)
\(=x\left(x^2+2xy+y^2-9\right)\)
\(=x\left[\left(x+y\right)^2-3^2\right]\)
\(=x\left(x+y+3\right)\left(x+y-3\right)\)
\(c,\text{ }14x^2y-21xy^2+28x^2y\)
\(=7xy\left(2x-3y+4x\right)\)
\(=7xy\left(6x-3y\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, Ta có: \(x^3+2x^2y+xy^2-4x\)
\(=x\left(x^2+2xy+y^2-4\right)\)
\(=x\left[\left(x+y\right)^2-2^2\right]\)
\(=x\left(x+y+2\right)\left(x+y-2\right)\)
b, Ý này dễ lắm, cậu tự làm nha!!!
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x(y - x)3 + y(x - y)2 + xy(x - y)
= x(y - x).(y - x)2 + y(x - y)2 + xy(x - y)
= x(y - x)(x - y)2 + y(x - y)2 + xy(x - y)
= (x - y)[x(y - x)(x - y) + y(x - y) + xy]
= (x - y)[x(y - x)(x - y) + y(x - y) + xy]
b) 3a2x - 3a2y + abx - aby
= 3a2(x - y) + ab(x - y)
= a(x - y)(3a + b)
a) x( y - x )3 - y( x - y )2 + xy( x - y )
= -x( x - y )3 - y( x - y )2 + xy( x - y )
= ( x - y )[ -x( x - y )2 - y( x - y ) + xy ]
= ( x - y )[ -x( x2 - 2xy + y2 ) - yx + y2 + xy ]
= ( x - y )( -x3 + 2x2y - xy2 - yx + y2 + xy )
= ( x - y )( -x3 + 2x2y - xy2 + y2 )
b) 3a2x - 3a2y + abx - aby
= 3a2( x - y ) + ab( x - y )
= ( x - y )( 3a2 + ab )
= ( x - y )a( 3a + b )
![](https://rs.olm.vn/images/avt/0.png?1311)
x3 -2x2 +x- xy2
= x ( x2 - 2x + 1 - y2)
= x\(\left[\left(x-1\right)^2-y^2\right]\)
= x ( x- 1- y) ( x - 1 + y )
X3-2x2+x-xy2
=(x3+x)-(2x2-xy2)
=x(x2+1)-x(2x-y2)
=x(x2-2x+1-y2)
=x[(x-1)2-y]
=x(x-1-y)(x-1+y)
Chúc bạn làm tốt@"
\(x^3+2x^2y+xy^2\)
\(=x\left(x^2+2xy+y^2\right)\)
\(=x\left(x+y\right)^2\)
\(x^3+2x^2y+xy^2\\ =\left(x^3+x^2y\right)+\left(x^2y+xy^2\right)\\ =x^2\left(x+y\right)+xy\left(x+y\right)\\ =\left(x^2+xy\right)\left(x+y\right)\)